New pyrimidine-amide-tetrazole ligand derived polyoxometalate-based copper complexes as catalysts for sulfide-sulfoxide transformation and electrochemical sensors - Lu, Jun-Jun; Lin, Hong-Yan; Liu, Qian-Qian; Liu, Xiao-Dong; Wang, Xiu-Li (CrystEngComm, 2023)
In this study, a new ligand, 5-(4-pyrimidinecarboxamido)-1 H -tetrazol (4-H 2 pat), was synthesized by connecting the pyrimidine group and tetrazole group through an amide bond for the first time, aiming to construct new POM-based metal-organic complexes (POMOCs). By using the ligand 4-H 2 pat, two new POMOCs, [Cu 4 (4-pat) 2 (μ 2 -OH)(CrMo 6 (OH) 6 O 18 )(H 2 O) 3 ]·2H 2 O ( 1 ) and [Cu 2 (4-pat)(β-Mo 8 O 26 ) 0.5 (H 2 O) 3 ] ( 2 ), were successfully synthesized under solvothermal and hydrothermal conditions, respectively. The structures were characterized by single crystal X-ray diffraction analysis, IR spectroscopy and powder X-ray diffraction (PXRD). In complex 1 , the 1D [Cu 4 (μ 2 -OH)(4-pat) 2 ] n 3 n + metal-organic chains were connected by μ 2 -bridging [CrMo 6 (OH) 6 O 18 ] 3− (CrMo 6 ) anions to construct a 2D layered structure. In complex 2 , the 2D [Cu 2 (4-pat)] n 2 n + metal-organic grid framework was consolidated by the μ 4 -bridging [β-Mo 8 O 26 ] 4− (Mo 8 ) anions. The use of two different POM anion clusters results in the formation of two diverse 2D framework structures. Complexes 1 and 2 can effectively catalyze the oxidation of methyl phenyl sulfide as non-homogeneous catalysts with 97% and 95% conversions, respectively. They can also be used as electrocatalysts to prepare bulk-modified electrodes for detecting Cr( vi ) and Fe( iii ) ions with low detection limits. In addition, the effects of different POMs on the structures and catalytic/electrocatalytic performances of the title complexes were discussed. A new organic ligand was constructed by linking pyrimidine and tetrazole group through amide bond and used to build POM-based metal-organic complexes that can be used as catalysts for the catalytic oxidation of sulfides and electrochemical sensors.